Penerapan Pendekatan Pendidikan Matematika Realistik Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa - Rismawati Rismawati; Elsa Komala (Universitas Sarjanawiyata Tamansiswa, 2018)
The purpose of this study is to determine the achievement and improvement of students' mathematical problem solving skills using learning approaches Realistic Mathematics Education, as well as to know the attitude of students using the approach of learning Realistic Mathematics Education. The research method is quasi experiment with Nonequivalent group pretest-postest design. The experimental class gained learning with the approach of Realistic Mathematics Education and control class with ordinary learning. The population of the study were students of class VIII MTs Negeri 1 Cianjur. The samples used as many as 2 classes from eight classes were chosen by purposive sampling technique. To get the data of research result used the test instrument of mathematical problem solving ability and student questionnaire. Data processing achievement of students 'mathematical problem solving ability using percentage of students posttest score, improvement of students' mathematical problem solving ability using Mann-Whitney, student attitude data using percentage of questionnaire answer each student. Based on data analysis, the achievement of students' mathematical problem solving ability using the approach of Realistic Mathematics Education is very low, the achievement of students using the usual learning is very low, the improvement of students' mathematical problem solving skills using the Realistic Mathematics Education approach is better than the improvement of students' mathematical problem solving ability using ordinary learning with medium category, and student attitude toward learning using Realistic Mathematics Education approach is mostly positive.Keywords: Approach to Realistic Mathematical Education (RME), Mathematical Problem Solving.